2018
DOI: 10.2217/epi-2018-0001
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation and Gene Expression Profiling Reveal MFAP5 as a Regulatory Driver of Extracellular Matrix Remodeling in Varicose Vein Disease

Abstract: A coherent model proposed incorporates the relevant signaling networks and will hopefully aid further studies on varicose vein pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 65 publications
1
11
0
4
Order By: Relevance
“…Its product is involved in the inflammatory response in the vascular wall, stimulating the production of the chemokine MCP-1 (Satonaka et al, 2004), which is consistent with the modern view of the pathogenesis of chronic venous disease (Lim, Davies, 2009;del Rio Solá et al, 2009). Additionally, Smetanina and co-workers demonstrated enhanced PPP3R1 expression in VV specimens compared to unaffected veins (Smetanina et al, 2018). In addition to gene prioritization, SMR-HEIDI was used to search for traits associated with VV-related functional variants.…”
supporting
confidence: 54%
“…Its product is involved in the inflammatory response in the vascular wall, stimulating the production of the chemokine MCP-1 (Satonaka et al, 2004), which is consistent with the modern view of the pathogenesis of chronic venous disease (Lim, Davies, 2009;del Rio Solá et al, 2009). Additionally, Smetanina and co-workers demonstrated enhanced PPP3R1 expression in VV specimens compared to unaffected veins (Smetanina et al, 2018). In addition to gene prioritization, SMR-HEIDI was used to search for traits associated with VV-related functional variants.…”
supporting
confidence: 54%
“…In particular, it induces MCP-1 production, which was shown to be enhanced in VVs 55 , 56 . Finally, a recent study demonstrated that expression of PPP3R1 is increased in the venous tissue of VVs patients compared with veins of healthy individuals (fold change = 1.5) 57 .…”
Section: Resultsmentioning
confidence: 90%
“…In particular, it induces MCP-1 production, which was shown to be enhanced in VVs [28, 29]. Finally, a recent study demonstrated that expression of PPP3R1 is increased in the varicose veins as compared to normal veins (fold change = 1.5) [30]. For the locus on chromosome 16, literature data along with DEPICT analysis strongly suggest the involvement of the PIEZO1 gene.…”
Section: Resultsmentioning
confidence: 99%